Experimental Approach to Monitoring the Degradation Status of Pipelines Transporting Hydrocarbons (European Journal of Engineering Science and Technology, 2021)
Improve the reliability of the gas and oil transportation process is a primary objective of the pipeline designers because it interests the safety of the goods and the people, the availability and the performance of pipelines as well as the economy of the hydrocarbon transport. Corrosion is a present phenomenon that occurs inside and outside of buried pipes, causing the pipeline to be pierced, leading to gas and oil leaks and causes consequences of the major economic losses. In this context, our study focused on the corrosion monitoring of metals used in the transport of hydrocarbons by two approaches based on electrochemical techniques. Monitoring the evolution of the corrosion potential using an elaborated reference instead of a commercial reference electrode, and by electrochemical impedance spectroscopy (EIS) coupled with the gravimetric method. The obtained results showed the efficiency of our approach for the realization of a corrosion sensor intended for the monitoring of corrosion in pipelines.